Development of a networked car racing game based on a standalone car racing game - Wang, Yiyuan. (2011)
Setting up a client server based distributed environment is the basic step of testing some interest management algorithms. This distributed system can be simply a networked car racing game modified from a standalone racing game. The purpose of my project is to build such a networked game based on an open source standalone game.